PENGEMBANGAN MEDIA ANIMASI INTERAKTIF BERBASIS CANVA PADA MATERI IKLIM DAN PERUBAHAN IKLIM PADA PESERTA DIDIK KELAS 4 SD - Rahayu, Sri Rahayu Ningsih; Ariesta Wulandari Ciptaningtyas; Hedin Hendratarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was carried out from the problem of the lack of use of interactive visual media in elementary schools, especially in abstract materials such as climate and its changes which often make it difficult for students to understand. The limitations of educators in mastering learning technology result in the teaching and learning process tending to be conventional, thereby reducing student interest and involvement, this research is inferred to create interactive animation learning media innovations using the Canva application for students, as well as test the level of eligibility. This research uses a methodology by applying Research and Development (R&D) methods, the focus of this research includes comprehensive product development and expert validation. Validation is carried out by material experts and media experts with the aim of evaluating the quality of content, visual aspects, and relevance of media to curriculum goals. Data collection was carried out through Likert scale questionnaires, direct observations, and literature reviews, which were then processed through quantitative descriptive analysis using detailed percentage calculations. The results of the study prove that Canva is an effective tool for creating interactive animations that are attractive and easy to understand. The level of media feasibility reached a very significant number, namely 93.33% of the media and of the material 99.33%, which categorized this animation as "very feasible" media. Based on the results of the study, Canva-based interactive animation has proven to be an innovative solution that can increase students' understanding of concepts and active participation in science subjects. This media not only overcomes the obstacles of technological limitations for educators, but also provides a more concrete, dynamic, educational, and fun learning experience for students at the elementary school level, this aims to achieve the best and maximum learning outcomes in the long term for the advancement of the quality of Indonesia's national education.